Pengaruh Konsep Geografi melalui Pembelajaran IPAS Kelas 4 SD - Ornella Alika (Pena Edukasia, 2024)
The influence of geography concepts in social studies learning in grade 4. Geography helps students understand the world around them and human interaction with the environment. Learning geography in primary school is important to develop curiosity and environmental awareness. The integration of geography in IPAS learning provides a comprehensive understanding of everyday life. This paper explains the importance of introducing geography concepts, integrating geography in IPAS subjects, and effective geography learning. Good geography learning helps students develop 21st century skills, thus providing guidance for primary school teachers to develop relevant learning.